Transition of care from paediatric to adult rheumatology - McDonagh, Janet E (BMJ Group, 2007)
The origin of paediatric rheumatology in the UK mainly lies in adult rheumatology and this has proved invaluable in terms of transition provision, education and training, and collaborative research. The last 5 years have seen adolescent rheumatology gather momentum with the creation of an objective evidence base, a sound foundation for future work addressing the many unanswered questions and hypotheses in the area of transitional care. The aim of this paper is to review the evidence supporting the recent developments in transitional care within rheumatology. Acknowledging the non‐categorical nature of transition, the author will also refer to evidence from other chronic illnesses which has informed these developments.